Splenic Littoral Cell Angioma. Case Report; Angioma Esplénico de Células Litorales. Reporte Caso - Gonzalez-Palacios, L (Sociedad de Cirujanos de Chile, 2025)
Objective: To describe the clinical, imaging, and surgical findings of a patient who underwent splenectomy for suspected lymphoma, whose postoperative analysis revealed a splenic littoral cell angioma. Materials and Methods: Information was obtained from the patient’s clinical record, and a literature review was conducted using the terms: “splenic littoral cell angioma,” “laparoscopic splenectomy,” and “splenic tumor.” Results: 37-year-old female patient referred for suspected splenic lymphoma following a CT scan that showed multiple hypodense lesions. The differential diagnosis included granulomatous diseases or lymphoproliferative syndromes. A laparoscopic splenectomy was performed, and the pathological report showed multifocal involvement by littoral cell angioma, with immunohistochemistry positive for CD31, CD68, and CD117. Discussion: The use of advanced imaging studies has increased incidental findings of solid tumors of the spleen. Littoral cell angioma is a benign vascular tumor of low incidence, imaging characteristics can be confused with other conditions. Management includes surgical treatment and imaging follow-up based on the characteristics and presentation. © 2025, Sociedad de Cirujanos de Chile. All rights reserved.